Approaches to mobile application development: comparative performance analysis - Delía, Lisandro Nahuel (2017)
The purpose of software development is meeting both functional and non-functional requirements. In mobile device applications, non-functional requirements are more relevant due to the restrictions inherent to these devices. The performance of a mobile application affects user preference for use. In this article, we present a performance study of the approaches used to develop software for mobile devices for the two currently more commonly used operating systems: iOS and Android. The results obtained are analyzed, and conclusions supported by the tests carried out are drawn.